PRELIMINARY RESULTS REGARDING THE ROCK FALLS OF DECEMBER 17, 2009 AT TEMPI, GREECE - Christaras, B.; Papathanassiou, G.; Vouvalidis, K.; Pavlides, S. (Bulletin of the Geological Society of Greece, 2010)
On December 17, 2009, a large size rock fall generated at the area of Tempi, Central Greece causing one casualty. In particular, a large block was detached from a high of 70 meters and started to roll downslope and gradually became a rock slide. About 120 tones of rock material moved downward to the road resulting to the close of the national road. Few days after the slope failure, a field survey organized by the Department of Geology, AUTH took place in order to evaluate the rock fall hazard in the area and to define the triggering causal factors. As an outcome, we concluded that the heavily broken rock mass and the heavy rain-falls, of the previous days, contribute significantly to the generation of the slope failure. The rocky slope was limited stable and the high joint water pressure caused the failure of the slope.